Pillow Talk - Kovačević, Sonja Anna, 1981- (2017)
Pillow Talk works as a listening device set to engage the public with the lives of asylum seekers and refugees in Iceland. The setup is simple: several emergency beds from the Red Cross, that serve as beds for asylum seekers in Iceland, are travelling the city. They are equipped with speakers and are broadcasting an array of stories. The audience is invited to lie down and listen. The stories have been carefully edited to give an insight into the person portrayed and are looking to find new ways of engaging with the ‘story of a refugee’. Through lying down in the bed, shifting their bodies and having the sensory stimulation the audience is invited to experience a new way of connectedness to the topic. Pillow Talk is in line with an ongoing working process of Sonja Kovačević reflecting the role theatre can play in modern democracies. How can theatre serve as an oratory, giving a voice to people? How can it give space to marginalized groups in society without taking advantage of them? Can there be social inclusion of refugees into society? How can you engage the audience with the topic in a way that connects their whole body, that touches their senses and not only their intellect? These questions played a vital part in the development of the project. The use of ‘story’ when working on art with refugees became a center point of the research and the piece itself. Any narrative or life story by a refugee is already framed and defined by the person’s definition as a refugee. Their status already frames them as traumatized victims. What is often forgotten is that even though a person suffered a traumatic event, this doesn’t take away anything of their personhood. We are accustomed to look at people who become victimized through a lens of compassion and pity, and often this is being enforced by aid organizations. On the other hand, ‘story’ can also be used as a tool to help refugees frame their life story for themselves. It can be helpful for people who went through traumatic events to find ways to own their story, ...